Centrifugal lipodystrophy on a spectrum with lupus erythematosus panniculitis in children and efficacy and safety of hydroxychloroquine: A clinicopathological study. Issue 11 (27th September 2022) - Xu, Qianyue; Qiu, Yangyang; Lu, Zhiyong; Yu, Hong; Ling, Bo; Li, Yan; Gu, Yan; Yao, Zhirong
Abstract: This study aimed to investigate the relationship between centrifugal lipodystrophy (CLD) and lupus erythematosus panniculitis (LEP), and the efficacy and safety of hydroxychloroquine (HCQ) for treating CLD in children. A total of 29 cases clinically diagnosed as CLD ( n  = 24) and CLD/LEP overlap ( n  = 5) were enrolled and all were confirmed by skin biopsies of CLD and LEP. The clinicopathological findings, clinical outcomes, and prognosis with the treatment of HCQ between CLD and LEP were compared. All 29 cases (male: female = 1:1.6; median age at onset: 3 years) had cutaneous lesions of centrifugally expanding lipoatrophy, of which five cases overlapped with LEP lesions presented as erythematous indurated plaque ( n  = 2), subcutaneous nodules ( n  = 2) and alopecia along Blaschko's lines ( n  = 1). Antinuclear antibodies were found in six (25.0%) CLD and two (40.0%) overlapped patients ( p  = 0.597). Histopathologically, of the 24 cases of CLD, 14 (58.5%) exhibited subcutis loss or mild lobular inflammation. Ten (41.7%) cases displayed lobular panniculitis with moderate to dense lymphohistiocytic infiltrate and plasma cells, similar to the five cases of overlap. Small clusters of CD123 positive plasmacytoid dendritic cells were found in 62.5% (5/8) of CLD and 66.7% (2/3) of overlap cases ( p  > 0.99). HCQ (5 mg/kg/d) treatment showed improvement in 91.3% (21/23) of CLD and all overlap cases, including four cases unresponsive to previous oral glucocorticosteroid treatment. Our findings suggested that CLD and LEP represent a spectrum within the same disease. HCQ (5 mg/kg/d) was effective and safe for treating CLD (age >1.5 years), and early treatment and a regular long‐term follow‐up are essential.